The impact of fish feeding habits and thermal conditions on plankton body size fluctuations: Commentary perspective - Moshe Gophen (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2019)
The impact of Temperature and other physical parameters on the size of planktonic organisms is widely known. The paper is focused on the impact of fish feeding habits on the phytoplankton and zooplankton body size in Lake Kinneret. The issue is comparatively considered with its implications in the marine environment. The study is relevant within the actual global trend of climate change of warming impact on freshwater and marine biota. Principal conclusion is that the planktonic organisms body size, in freshwater or marine ecosystems, is a dependant of complex interaction with significant impact of fish feeding habits. The most common species, the Bleaks, is a zooplanktivorous feeder through all its life cycle stages; Young stages (<5g) of Sarotherodon galilaeus are zooplanktivore whilst older stages are filter feeders which preferably utilize Peridinium if available but increased density of zooplankton prey was documented since late 1990's after the decline of Peridinium availability. The complexity of the processes involved include chemical, physical and biological conditions which are prominently related to temperature and fish consumption.